Impact of experiential dementia care learning on knowledge, skills and attitudes of nursing students: A systematic literature review - Adewuyi, Modupe; Morales, Kathleen; Lindsey, Anna (Nurse education in practice, 2022)
The aim of this systematic review was to synthesize evidence on the effect of clinical experiential learning approaches on pre-licensure nursing students' competence in dementia care and to identify associated challenges. As the prevalence of dementia increases, nurse educators must proactively prepare pre-licensure nursing students to care for people living with dementia. The limited number of physical clinical learning settings, especially during the current COVID-19 pandemic, has caused many nursing programs to use alternative experiential learning approaches. Systematic Literature Review In accordance with PRISMA guidelines, we conducted a systematic search for the literature in Cumulative Index to Nursing and Allied Health Literature, MEDLINE and ProQuest for relevant peer-reviewed studies published between 2010 and 2021. Using the Boolean operator search approach, the keyword "dementia care" was combined with "AND/OR" and other search terms. In addition, a descendent and an ascendent search were conducted to find other relevant studies. A total of 17 retrieved articles met the inclusion criteria. Five themes emerged, with the main findings being that face-to-face (in person), virtual and simulated experiential learning approaches increased pre-licensure nursing students' dementia care knowledge. However, the face-to-face experiential learning approach that provides physical contact with people living with dementia and clinical staff had more impact on their skills and attitudes. The evidence in this review could inform curriculum development, teaching methods, experiential learning experiences and clinical placements of pre-licensure nursing students with regards to dementia care. More research is needed to explore further the impact of virtual and simulated experiential learning approaches on pre-licensure nursing students' dementia care skills. This systematic literature review synthesizes evidence of clinical experiential learning on prelicensure nursing students' competence in dementia care per PRISMA guidelines. Five themes emerged #dementia #experientiallearning #prelicensurenursingstudents #clinicalsducation